A failure-mode based anisomorphic constant life diagram for a unidirectional carbon/epoxy laminate under off-axis fatigue loading at room temperature. (March 2014) - Kawai, M; Itoh, N
The off-axis constant fatigue life diagrams for a unidirectional carbon/epoxy laminate in different fiber orientations are identified over the whole range of stress ratio. The experimental results show that the off-axis constant fatigue life diagram plotted in the plane of alternating and mean stresses tends to shrink and incline to the left of the alternating stress axis more significantly as the off-axis angle of a specimen increases. The overall shapes of the off-axis constant fatigue life envelopes for different constant values of life are highly non-linear and asymmetric about the alternating stress axis, regardless of fiber orientation. These observations suggest that the sensitivity to mean stress in off-axis fatigue differs depending on the mode of fatigue loading, i.e. tension–tension, tension–compression, and compression–compression loading, and the difference is associated with the different modes of failure under different modes of fatigue loading. To deal with the off-axis fatigue strength of a unidirectional composite for any fiber orientation over the whole range of stress ratio, a most general form of the anisomorphic constant fatigue life diagram is developed that can take into account different sensitivities to mean stress in fatigue and distinguish between the tensile- and compressive-dominated failure modes. It is demonstrated that the generalized anisomorphic constant fatigue life diagram allows accommodating itself to a significant change in shape of a constant fatigue life envelope that depends on the range of stress ratio, and thus it can successfully be applied to accurate description of the off-axis constant fatigue life diagram for the unidirectional carbon fiber reinforced plastic laminate, regardless of fiber orientation.